2021
DOI: 10.1093/gbe/evab048
|View full text |Cite
|
Sign up to set email alerts
|

Large Genetic Diversity and Strong Positive Selection in F-Box and GPCR Genes among the Wild Isolates of Caenorhabditis elegans

Abstract: The F-box and chemosensory GPCR (csGPCR) gene families are greatly expanded in nematodes, including the model organism Caenorhabditis elegans, compared to insects and vertebrates. However, the intraspecific evolution of these two gene families in nematodes remain unexamined. In this study, we analyzed the genomic sequences of 330 recently sequenced wild isolates of C. elegans using a range of population genetics approaches. We found that F-box and csGPCR genes, especially the Srw family csGPCRs, showed much mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 70 publications
(89 reference statements)
1
4
0
Order By: Relevance
“…5C). Thus, our studies with the SVs support the findings of previous studies (34, 35) using the SNVs that some Hawaiian strains carry ancestral variants that are highly divergent, while other Hawaiian strains (Hawaii_4-7 groups) are admixed with the European groups.…”
Section: Resultssupporting
confidence: 90%
“…5C). Thus, our studies with the SVs support the findings of previous studies (34, 35) using the SNVs that some Hawaiian strains carry ancestral variants that are highly divergent, while other Hawaiian strains (Hawaii_4-7 groups) are admixed with the European groups.…”
Section: Resultssupporting
confidence: 90%
“…To understand the evolution of STRs in C. elegans , a more informative comparison might come from choosing a reference from strains that avoided selective sweeps and was isolated from regions nearby the species origins. For example, the Hawaiian strain XZ1516, which likely carries the most ancestral genotypes ( Crombie et al 2019 ; Ma et al 2021 ), has contraction in 66% of the 2400 pSTRs that showed length variation to the reference STRs. Therefore, STR expansion rather than contraction likely occurred from ancestors to descendants in C. elegans if we consider strains that might reflect the ancestral origin of the species.…”
Section: Discussionmentioning
confidence: 99%
“…In yeast we observe terms associated with cell cycle and plasma membrane among others Supplementary Figure S7a ), whereas in C. elegans , we observe enrichment for terms associated with detection of chemical stimuli, the plasma membrane and sensory perception ( Supplementary Figure S7b ). There is evidence supporting strong positive selection for sensory perception genes in C. elegans ( 19 ), reinforcing the notion that quasi-prime peptides are also associated with rapid, adaptive evolution.…”
Section: Resultsmentioning
confidence: 57%